Proline-Functionalised Calix[4]arene: An Anion-Triggered Hydrogelator - Becker, Thomas; Goh, C.; Jones, Franca; McIldowie, M.; Mocerino, Mauro; Ogden, Mark (The Royal Society of Chemistry, 2008)
A water-soluble, chiral calix[4]arene has been found to form hydrogels when triggered by the presence of specific anions, with efficacy linked to the Hofmeister series; the gel properties are modified by the associated cations, and gelation can be reversibly switched off by increasing pH.